Syntheses of ruthenium complexes for studies on water oxidation and their immobilization approaches - Söyler, Hatice

Photocatalytic water reduction systems based on iridium and non-noble metal complexes - Tünnermann, Maike

Diferrate [Fe2(CO)6(μ-CO){μ-P(aryl)2}]− as Self-Assembling Iron/Phosphor-Based Catalyst for the Hydrogen Evolution Reaction in Photocatalytic Proton Reduction-Spectroscopic Insights - Fischer, Steffen; Rösel, Arend; Kammer, Anja; Barsch, Enrico; Schoch, Roland; Junge, Henrik; Bauer, Matthias; Beller, Matthias; Ludwig, Ralf (Chemistry - A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Understanding and exploiting long-lived near-infrared emission of a molecular ruby - Otto, Sven; Dorn, Matthias; Förster, Christoph; Bauer, Matthias; Seitz, Michael; Heinze, Katja (Coordination Chemistry Reviews)
Keywords: Materials Chemistry; Physical and Theoretical Chemistry; Inorganic Chemistry

Structure–function relationship during CO2 methanation over Rh/Al2O3 and Rh/SiO2 catalysts under atmospheric pressure conditions - Martin, Natalia M.; Hemmingsson, Felix; Wang, Xueting; Merte, Lindsay R.; Hejral, Uta; Gustafson, Johan; Skoglundh, Magnus; Meira, Debora Motta; Dippel, Ann-Christin; Gutowski, Olof; Bauer, Matthias; Carlsson, Per-Anders (Catalysis Science & Technology)
Intermediate species formed during CO2 methanation over Rh/Al2O3 and Rh/SiO2 catalysts.
Keywords: Catalysis

A Straightforward Synthesis to Novel 1,10-Phenanthrolines with Fused Thiophene Structure - Bauer, Matthias; Tünnermann, Maike; Rehsies, Pia; Flörke, Ulrich (Synlett)
We report here a straightforward synthesis for a series of new structures with fused 1,10-phenanthroline-thiophene connection. They are synthesized with a modified Hinsberg thiophene procedure, followed by successive modification to yield several 5,7-disubstituted thieno[3,4-f][1,10]phenanthrolines, most notable thiophene-substituted compounds that could be potentially of use for organic electronics applications. For some selected examples, crystal structures were obtained, showing a nearly coplanar arrangement around the fused connection, also beneficial for an effective electron transfer in organic electronics or solar cells.
Keywords: Organic Chemistry

The Bonding Situation in the Dinuclear Tetra-Hydrido Complex [{5CpFe}2(μ-H)4] Revisited by Hard X-Ray Spectroscopy - Burkhardt, Lukas; Mueller, Carsten; Groß, Oliver A.; Sun, Yu; Sitzmann, Helmut; Bauer, Matthias (Inorganic Chemistry)
Keywords: Inorganic Chemistry; Physical and Theoretical Chemistry

Entwicklung und Synthese von Ein- und Mehrkomponentensystemen zur photokatalytischen Wasserreduktion - Meinhardt, Regina

Selective pore filling of mesoporous CMK-5 carbon studied by XRD: Comparison between theoretical simulations and experimental results - Weinberger, Christian; Hartmann, Marc; Ren, Sai; Sandberg, Thomas; Smått, Jan-Henrik; Tiemann, Michael (Microporous and Mesoporous Materials)
It is possible to infiltrate a guest species selectively in one pore system of bimodal mesoporous CMK-5 carbon by an optimized nanocasting procedure. The selective filling has a drastic impact on the low-angle X-ray diffraction pattern of this novel class of materials. The structures of CMK-5, CMK-5 composite materials (sulfur and SnO2 as guest species), and CMK-3 carbon were simulated to investigate the influence of the pore filling with different guest species on the diffraction pattern and compared with experimental results. Additionally, the impact of structural defects is taken into account. The nature of the guest species strongly influences the relative intensity of the diffraction peaks. It turns out that the diffraction patterns of sulfur-carbon composite materials are nearly identical as those of CMK-3 carbon, which is attributed to a similar electron density of carbon and sulfur. Thus, sulfur is an ideal guest species to investigate the selective pore filling in CMK-5 carbon.

Porous Aluminum Oxide and Magnesium Oxide Films Using Organic Hydrogels as Structure Matrices - Chen, Zimei; Kuckling, Dirk; Tiemann, Michael (Nanomaterials)
We describe the synthesis of mesoporous Al2O3 and MgO layers on silicon wafer substrates by using poly(dimethylacrylamide) hydrogels as porogenic matrices. Hydrogel films are prepared by spreading the polymer through spin-coating, followed by photo-cross-linking and anchoring to the substrate surface. The metal oxides are obtained by swelling the hydrogels in the respective metal nitrate solutions and subsequent thermal conversion. Combustion of the hydrogel results in mesoporous metal oxide layers with thicknesses in the μm range and high specific surface areas up to 558 m2∙g−1. Materials are characterized by SEM, FIB ablation, EDX, and Kr physisorption porosimetry.

Bimodal Mesoporous CMK-5 Carbon: Selective Pore Filling with Sulfur and SnO2 for Lithium Battery Electrodes - Weinberger, Christian; Ren, Sai; Hartmann, Marc; Wagner, Thorsten; Karaman, Didem. Ş.; Rosenholm, Jessica M.; Tiemann, Michael (ACS Applied Nano Materials)
Ordered mesoporous CMK-5 carbon exhibits two distinct pore systems that can be modified individually. This work demonstrates how one of the pore systems can be selectively filled with elemental sulfur, while the other pore system remains empty. The resulting sulfur–carbon composite material with high residual porosity can be used as the cathode material in lithium–sulfur battery cells. We present a systematic investigation of the loading of CMK-5 carbon with variable relative amounts of sulfur and compare the results to the preparation of SnO2 (as well as TiO2, Mn2O3/Mn3O4, NiO) nanoparticle-loaded CMK-5 carbon.

Hydrogels as Porogens for Nanoporous Inorganic Materials - Weinberger, Christian; Kuckling, Dirk; Tiemann, Michael (Gels)
Organic polymer-hydrogels are known to be capable of directing the nucleation and growth of inorganic materials, such as silica, metal oxides, apatite or metal chalcogenides. This approach can be exploited in the synthesis of materials that exhibit defined nanoporosity. When the organic polymer-based hydrogel is incorporated in the inorganic product, a composite is formed from which the organic component may be selectively removed, yielding nanopores in the inorganic product. Such porogenic impact resembles the concept of using soft or hard templates for porous materials. This micro-review provides a survey of select examples from the literature.

Impact of finite-temperature and condensed-phase effects on theoretical X-ray absorption spectra of transition metal complexes - Müller, Patrick; Karhan, Kristof; Krack, Matthias; Gerstmann, Uwe; Schmidt, Wolf Gero; Bauer, Matthias; Kühne, Thomas D. (Journal of Computational Chemistry)

Graphene oxide as flexibilizer for epoxy amine resins - Wolk, Andreas; Rosenthal, Marta; Weiß, Julia; Voigt, Markus; Wesendahl, Jan-Niklas; Hartmann, Marc; Grundmeier, Guido; Wilhelm, Rene; Meschut, Gerson; Tiemann, Michael; Bremser, Wolfgang (Progress in Organic Coatings)
Different types of reduced graphene oxide and graphene oxide particles have been studied regarding their influence on the curing behaviour of epoxy-amine resins. Especially the specific surface area of reduced graphene oxide was selectively influenced by controlled drying of the material. The different types of reduced graphene oxide particles were used to produce epoxy-amine composites that significantly change their curing behaviour and mechanical properties. A variety of surface areas and compositions were prepared by combination of a fast heating rate and different drying methods. The combination of freeze drying with a fast heating rate leads to a large specific surface area of 680 m2/g. The morphologies of the particles were observed by scanning electron microscope and the BET surface area was measured with nitrogen-physisorption. The exfoliation quality was measured by XRD. The generated graphene oxide and thermally reduced graphene oxide particles were mixed with epoxy-amine resin. The curing behaviour was studied with rheological and differential scanning calorimetry (DSC) measurements. We observed that different surface functionalities lowers the Glass transition temperature and the gel time of an epoxy-amine curing system. In addition, we found that generated graphene oxide acts as flexibilizer. An increase of the deformation from 2.5 mm to 3.1 mm was measured by Erichsen Cupping Test.

Detection and Characterization of Hydride Ligands in Iron Complexes by High-Resolution Hard X-ray Spectroscopy and Implications for Catalytic Processes - Burkhardt, Lukas; Holzwarth, Michael; Plietker, Bernd; Bauer, Matthias (Inorganic Chemistry)

Structure and reactivity of a mononuclear gold(II) complex - Preiß, Sebastian; Förster, Christoph; Otto, Sven; Bauer, Matthias; Müller, Patrick; Hinderberger, Dariush; Hashemi Haeri, Haleh; Carella, Luca; Heinze, Katja (Nature Chemistry)

Phenanthroline-basierte Kupferkomplexe für Wasserspaltungsanwendungen - Stührenberg, Kai

Kinetics of ozone decomposition in porous In2O3 monoliths - Klawinski, Danielle; Weinberger, Christian; Klaus, Dominik; Smått, Jan-Henrik; Tiemann, Michael; Wagner, Thorsten (Physical Chemistry Chemical Physics)
We determine ozone decomposition on indium oxide by utilizing the gas transducing properties of hierarchically porous monoliths.

Catalytic hydrogenation of CO2 to methane over supported Pd, Rh and Ni catalysts - Martin, Natalia M.; Velin, Peter; Skoglundh, Magnus; Bauer, Matthias; Carlsson, Per-Anders (Catalysis Science & Technology)
CO2 methanation over Rh/Al2O3, Rh/CeO2 and Ni/CeO2 at 350 °C highlighting the different surface speciation during reaction.
Keywords: Catalysis

Structural Transitions and Thermochromism of Linear Polynuclear Cobalt(II)-4-Octadecyl-1,2,4-triazole Complexes - Bräunlich, Irene; Mair, Christiane; Bauer, Matthias; Caseri, Walter (Journal of Inorganic and Organometallic Polymers and Materials)
Keywords: Materials Chemistry; Polymers and Plastics